Soil organic matter changes according to the application of organic and mineral fertilizers within long-term experiments - Monika CVETKOV; Anton TAJNŠEK (Acta Agriculturae Slovenica)
Within the long-term field experiments at IOSDV Jable near Ljubljana (subalpine climate, heavy hydromorphic silt loam) and at IOSDV Rakičan (Pannonian climate, sandy silt), the impact of organic matter management system and mineral nitrogen fertilization on the soil organic matter content was studied in the period 1998-2008. The following management systems were selected: system A - no organic matter, system B - farmyard manure ploughing in, system C - straw/catch crop ploughing in. Four different mineral N rates (N0, N1, N2, N3) were evaluated. During the three-year crop rotation, maize, wheat and barley (or, alternatively, oats) were sown each year. The annual balance of Corg was calculated on the basis of the quantity of added organic and mineral fertilizers, considering the quantity of Corg in the soil. In system A, at both locations, fertilizing with the highest amount of mineral N resulted in a higher Corg content. At both locations, positive effect of organic fertilization on the increase of the Corg content was registered where management systems with organic matter (i.e. systems B and C) applied, while statistically significant impact of mineral N on a higher Corg content was determined only in system C. Within all three systems, the highest Corg values were reached when the highest mineral N application volume was used. After 11 years, the Corg content in system A decreased irrespective of the mineral N fertilization at both locations. At IOSDV Jable, a small decrease of the Corg content was measured in BN0, while all other treatments at IOSDV Jable and at IOSDV Rakičan resulted in an increased Corg content.